FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT DALAM MENGKONSUMSI IKAN DI NAGARI DUKU KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Nurmega, Nurmega; Rianto, Slamet; Juita, Erna (Pendidikan Geografi, 2013)
This study aimed to obtain information, analyze and discuss data on the factors that influence people to consume fish at the Nagari Duku Koto XI Tarusan  Pesisir Selatan District. This type of research was descriptive correlational. The study population was a person who plays a housewife who represents families in Koto XI Tarusan  Pesisir Selatan District totaling 1,083 people. The study sample in this study was taken with proportional random sampling technique the large proportion of the sample is determined 10% so that the sample amounted to 108 households. Based on a simple linear regression analysis, double (multiple) and the correlation it can be concluded as follows: (1) there is the influence of the educational level of fish consumption in Nagari Duku Koto XI Tarusan  Pesisir Selatan District cause t observation> t table (3,037> 1,673), the power relationship is low (r = 0,283) and a very small contribution (8,0%), (2) the income level of the influences of fish consumption in Nagari Duku Koto XI Tarusan  Pesisir Selatan District cause t observation> t table (4,653> 1,673), power relations are categorized (r = 0,412) and the amount of the contribution is very small (17,0%), (3) there is no effect on the level of knowledge of fish consumption in Nagari Duku Koto XI Tarusan  Pesisir Selatan District cause t observation> t table (0,552 < 1,673), the strength of the relationship is very low (r = 0,053) and the amount of the contribution is very small (0,03%) and (4) There is the influence of the level of education, level of income and level of knowledge together to fish consumption in Nagari Duku Koto XI Tarusan  Pesisir Selatan District because F observation > F table (8,760> 2,773). Strength of the relationship between these three variables on fish consumption in Nagari Duku Koto XI Tarusan  Pesisir Selatan District includes medium category (r = 0,449), whereas the contribution is small (20,2%).